14 Winner of the marlow prize: Virtual realityreduced pain and anxiety for palliative care patients in an acute hospital setting: A service evaluation. (14th March 2023) - Burridge, Nancy; Sillence, Alison; Teape, Lynda; Clark, Ben; Bruce, Emma; Etkind, Simon
Abstract : Background: Virtual Reality (VR) provides an immersive computer generated 3-dimensional experience allowing the brain to perceive an entirely different environment and has positive effects in management of pain and anxiety in a variety of populations. Despite potential benefits there remains limited evidence regarding the feasibility and outcomes of VR in palliative care, particularly in the acute hospital setting. Methodology: We offered patients referred to a hospital-based specialist palliative care team, experiencing symptoms of pain or anxiety access to a VR intervention. This comprised of a short visual experience lasting approximately 7 minutes. Participants rated pain and anxiety on a 0–10 Likert scale immediately pre and post intervention and completed an evaluation form, including free text description of their experience. We analysed change in symptom scores using parametric statistics. Results: 28 participants (19 female, 9 male, age range 25 – 84 years) used the VR equipment a total of 42 times with no adverse events. Mean VAS pain score reduced by 28.6% from 4.10 (SD = 2.71) pre intervention, to 2.93 (SD=2.45) immediately post intervention (t(27)=5.150, p<0.001). Mean anxiety scores reduced by 40.3% from 4.43 (SD=2.56) to 2.65 (SD=2.24); t(27)=5.058, p<0.001. 23 participants completed a written evaluation, rating the overall experience on average as 4.7/5; All would recommend the experience to a friend. The VR experience was described as absorbing, relaxing, and distracting; Staff observed visible relaxation during usage. One patient reported it enabled them to undergo a painful intervention. One patient declined the VR experience as they were unable to tolerate the goggles. Conclusion: VR was largely well received and had a positive effect on pain, anxiety, and feelings of wellbeing. Larger scale evaluation with longer follow up and repeated exposure will generate important data on feasibility and patient outcomes.